Step 1

If we have three variables x,y, and z

And we make three linear equations with them then that is three linear equations in three unknowns.

Step 2

For example:

x+y+z=6

2x-y+z=3

x+y-z=0

If we solve the linear equations we will get x=1, y=2, and z=3

If we have three variables x,y, and z

And we make three linear equations with them then that is three linear equations in three unknowns.

Step 2

For example:

x+y+z=6

2x-y+z=3

x+y-z=0

If we solve the linear equations we will get x=1, y=2, and z=3